Heterogeneous nucleation of entrained eutectic Si in high purity melt spun Al-Si alloys investigated by entrained droplet technique and DSC. Issue 1 (March 2016) - Li, J H; Albu, M; Ludwig, T H; Hofer, F; Arnberg, L; Schumacher, P
Abstract: Entrained droplet technique and DSC analyses were employed to investigate the influence of trace elements of Sr, Eu and P on the heterogeneous nucleation of entrained eutectic Si in high purity melt spun Al-5wt.% Si alloys. Sr and Eu addition was found to exert negative effects on the nucleation process, while an increased undercooling was observed. This can be attributed to the formation of phosphide compounds having a lower free energy and hence may preferentially form compared to AlP. Only a trace P addition was found to have a profound effect on the nucleation process. The nucleation kinetics is discussed on the basis of the classical nucleation theory and the free growth model, respectively. The estimated AlP patch size was found to be sufficient for the free growth of Si to occur within the droplets, which strongly indicates that the nucleation of Si on an AlP patch or AlP particle is a limiting step for free growth. The maximum nucleation site density within one droplet is directly related to the size distribution of AlP particles or AlP patches for Si nucleation, but is independent of the cooling rates. Although the nucleation conditions were optimized in entrained droplet experiments, the observed mechanisms are also valid at moderate cooling conditions, such as in shape casting.